SOL-GEL METHOD BASED SYNTHESIS AND CHARACTERIZATION OF ZNO NANOPARTICLES (International Journal of Food and Nutritional Sciences, 2022)
In recent times, there has been a growing fascination with semiconductor material nanoparticles due to their distinctive properties and wide-ranging applications. Zinc oxide (ZnO), a semiconductor with a wide band gap (3.37eV), has garnered significant attention in the form of nano-sized particles. In the past decade, ZnO nanoparticles (NPs) have captivated researchers due to their favorable properties and potential applications in optoelectronic devices. This paper presents a study focused on the synthesis and characterization of ZnO nanoparticles using the sol-gel method. In this study, Zinc Oxide (ZnO) nanoparticles (NPs) were synthesized and classified using the sol-gel method. Deionized water served as the solvent, while Zinc Chloride (ZnCl2), Sodium Hydroxide (NaOH), and Zinc Acetate (Zn(CH3CO2)2) were employed as precursors. The prepared NPs were subjected to analysis to investigate their structural, morphological, optical, and magnetic properties. Techniques such as UV-VIS spectroscopy (Ultra Violet visible spectrum), X-ray Diffraction (XRD), and Scanning Electron Microscopy (SEM) were utilized for this purpose. SEM provided information about the particle size, UV-VIS spectroscopy yielded insights into the band energy of the particles, and XRD was employed to determine the average particle size and lattice contraction percentage of the ZnO NPs sample.